A Study to Assess the Effectiveness of Structured Teaching Programme on Knowledge among Adolescent Girls Regarding Urinary Tract Infection in Selected Community Area of Sursingdhar, Tehri Garhwal, Uttarakhand - Panwar, Shweta; Bisht, Soniya; Joshi, Durga; Negi, Neha; Pundir, Megha; Baby, Chand; Paliwa, Meena; Rawat, Ragini; Shah, Shikha; Kaira, Sunaina (Indian Journal of Nursing Sciences, 2024)
Aim: This study aims to assess the effectiveness of structured teaching program on knowledge among adolescent girls regarding urinary tract infection (UTI) in selected community of New Tehri, Uttarakhand. Methods: A pre-experimental research study with one group pre- and post-test pre-experimental design was used for this study. The sample consisted of 50 adolescent girls in selected community of Sursingdhar, New Tehri. They were selected by consecutive sampling technique. The data collected through questionnaire method. Results: The data were analyzed by descriptive and inferential statistics. Assessment of pre-test knowledge regarding UTI shows that 44% of the respondents had good knowledge while 38% of respondents had average knowledge whereas 10% and 8% reported excellent and poor knowledge, respectively, about UTI. Assessment of post-test knowledge shows that 78% of respondents had excellent knowledge, whereas 22% had good knowledge and 0% had poor and fair knowledge regarding UTI. The mean pretest knowledge score was 15.36 and mean percentage of pre-test was 30.72%.with standard deviation of 3.7837. The mean of post-test knowledge score was 21.88 and mean percentage of post-test was 43.76% with standard deviation of 2.191. The paired t-test value was used to find out effectiveness that is 20.72. The result shows that a significant difference between the mean pre-test and post-test (P < 0.05) structured teaching program was effective in improving the knowledge regarding UTI among adolescents girls. There is no association between sociodemographic variables with pre-test knowledge level score at 0.05 level of significance. Conclusion: The study highlights that students were able to gain knowledge about the UTI.